A STUDY ON EFFICIENCIES AND HINDRANCES TO BIM IMPLEMENTATION IN INDONESIAN CONSTRUCTION PROJECTS - Iis Roin Widiati; Ita Suhermin Ingsih; George Winaktu (Journal Innovation of Civil Engineering)
BIM is an integrated system where processes are conducted seamlessly, influencing information exchange not only among software but also among stakeholders. BIM is identified as a method that can be employed to enhance the efficacy and efficiency of construction projects, along with the quality of construction projects. The research aims to evaluate the effectiveness, challenges, and overall performance of BIM in the construction industry in Indonesia, providing insights into the extent to which BIM is utilized and its impact on construction projects in Indonesia. The research uses a literature review method to identify the BIM implementation process and its correlation with BIM maturity. The research results demonstrate the continued high demand for BIM resources among Indonesian construction projects. The use of BIM has been utilized in the construction, design, and planning phases of projects. The maturity of BIM utilization is predominantly associated with collaboration, team building, communication, and clash detection. BIM adoption is still quite low in Indonesia, particularly concerning legality, the availability of BIM requirements, supply chain participation, stakeholder involvement, and standard setting.